Sinergi Dakwah Mahasiswa STIBA Ar raayah dalam Safari Ramadhan: Penguatan Nilai Keislaman dan Kepedulian Sosial di Berbagai Daerah Di Nusantara - Dian Abdilah; Salam, Sahrun; Musliah; Raqiqatul Fuadi (Institut Muslim Cendekia, 2026)
The Safari Dakwah Ramadhan initiative represents a concrete manifestation of community engagement undertaken by students of the Sekolah Tinggi Ilmu Bahasa Arab (STIBA) Ar raayah. The program seeks to revitalize Islamic values, strengthen ukhuwah Islamiyah (Islamic brotherhood), and cultivate social awareness within Indonesian society. Implemented concurrently across various regions during the final ten days of Ramadan 1446 H, the program reflects the institution’s commitment to integrative religious and social development. The activities encompassed free iftar distribution, Islamic lectures, Qur’anic study circles, recitations, speeches, charitable contributions to orphans and the underprivileged, as well as interregional online discussions. The successful execution of these activities was made possible through the support of donors, local communities, and the collaborative spirit of the participating students. The community demonstrated strong enthusiasm and warmly welcomed the presence of young preachers, particularly due to the program’s tangible spiritual and social contributions. This study adopts a descriptive qualitative approach through field research, which aligns with the contextual characteristics of the Safari Dakwah Ramadhan program. The findings reveal that the Safari Dakwah program produced a positive and multidimensional impact on both the community and the student participants. The community exhibited heightened religious motivation and social awareness during Ramadan, while the students gained experiential learning that enriched their competencies in da’wah and leadership. This study concludes that a collaborative, humanistic, and educational model of da’wah can serve as an effective instrument for fostering a society grounded in faith, knowledge, and noble character.